2015
DOI: 10.1021/acsami.5b07294
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Nanocrystals—Bioactive Glass Hybrid Coating as Bone Substitutes by Electrophoretic Co-deposition: In Situ Control of Mineralization of Bioactive Glass and Enhancement of Osteoblastic Performance

Abstract: Surface functionalization of orthopedic implants is being intensively investigated to strengthen bone-to-implant contact and accelerate bone healing process. A hybrid coating, consisting of 45S5 bioactive glass (BG) individually wrapped and interconnected with fibrous cellulose nanocrystals (CNCs), is deposited on 316L stainless steel from aqueous suspension by a one-step electrophoretic deposition (EPD) process. Apart from the codeposition mechanism elucidated by means of zeta-potential and scanning electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 49 publications
1
46
0
Order By: Relevance
“…For instance, fibrous cellulose nanocrystals interconnected with bioactive glass are used to cover stainless steel. In vitro studies confirmed cell activity acceleration in terms of attachment, differentiation and mineralization [123]. On the other hand, the same cellulose surface has been enriched with BMP-2-coating to further increase the cell activity.…”
Section: Natural Polymersmentioning
confidence: 77%
“…For instance, fibrous cellulose nanocrystals interconnected with bioactive glass are used to cover stainless steel. In vitro studies confirmed cell activity acceleration in terms of attachment, differentiation and mineralization [123]. On the other hand, the same cellulose surface has been enriched with BMP-2-coating to further increase the cell activity.…”
Section: Natural Polymersmentioning
confidence: 77%
“…in combination with bioglass), have been shown to be suitable as orthopaedic materials. Such CNC-based hybrid materials can accelerate osteoblast attachment, increase their spreading, proliferation, even promote differentiation of mesenchymal cells towards the osteoblast like phenotype (Gorgieva et al 2017), as well as influence mineralization of the native osteoblast extracellular matrix positively (Chen et al 2015). Nevertheless, neither of these studies reports or even considers the internalization of materials (or their parts) by osteoblasts.…”
Section: Characterization Of Differently Modified Cncsmentioning
confidence: 99%
“…1,2 In particular, polymer based coatings can serve as drug delivery platforms, releasing biomolecules (antibiotics, growth factors, proteins, peptides, genes) preloaded into the coating matrix, to convert conventional implants into biologically active components. 3,4 In comparison with conventional oral or injectable therapies usually associated with side effects, such coating systems should be able to release drug molecules locally and in a controlled manner for prolonged periods.…”
Section: Introductionmentioning
confidence: 99%